Latin American poetry: intersections, translations, encounters - Evgraškina, Ekaterina; Jessen, Herle-Christin (Neuere Lyrik, 2023)
Die Veröffentlichung enthält ausgewählte Beiträge der Konferenz "Poetry today in Europe and Latin America - parallels, interactions, translations"
"This issue began with the 2019 conference 'Poetry today in Europe and Latin America - parallels, interactions, translations' ...We have since selected ten papers that we feel best represented the scope of the conference and its goals" - Introduction
Keywords: Aufsatzsammlung; Lyrik; Lateinamerika; Begegnung; Hispanoamerika